Developments in polyester composite materials – An in-depth review on natural fibres and nano fillers - Mahmoud Zaghloul, Mahmoud Yousry; Yousry Zaghloul, Moustafa Mahmoud; Yousry Zaghloul, Mai Mahmoud (Composite structures, 2021)
Recently, scientists are facing major obstacles in terms of selecting compatible filler materials for the sake of improving the performance of polymeric composite materials. Therefore, a high interest has been devoted to the development of polymeric composites reinforced with nano fillers. The nano reinforced particle’ polyester matrix composites (PMCs) are widely utilized in the manufacturing industries due to their high fracture toughness, light weight, superior strength to weight ratio, high tensile properties, high fatigue resistance, and improved corrosion resistance to severe environments. This article presents a review of the different manufacturing processes and the various reinforcing elements used throughout the preparation of PMCs. The affecting conditions during manufacturing of reinforced particle PMCs are deliberated in a manner to better understand the usefulness of incorporating reinforcing particles in PMCs. The natural fibres utilized as reinforcements in polyester composite materials are thoroughly reviewed including cotton, banana, jute, kenaf, coir, hemp, and sisal. The nano particles reviewed in this paper are nano clay, carbon nano tubes, nano graphene and nano graphene oxide. The reviewed material systems forming polyester nano composites are analysed separately and jointly, showing their scientific developments. The general mechanical characteristics as tensile, compression, fatigue, hardness, and flexural strength, etc. reported by other researchers are investigated with a main objective to demonstrate the quantity of reinforcement used and the corresponding improvements achieved after processing. Finally, the presented review aims to open the horizons towards applications and possible future prospects of natural fibres reinforced polymeric nano composites.